PENERAPAN PEMBELAJARAN KONTEKSTUAL DENGAN TEKNIK FOTO BERITA UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN - Rojik Susanto (EDU-KATA, 2018)
This study was conducted with the aim to describe (1) the activity of teachers in improving the ability of knowledge about the intrinsic elements of short stories, (2) the activity of student, (3) the results of student learning, and (4) response class IX students odd semester MTs Irsyadul Athfal District of Benjeng District Gresik 2011/2012 school year to learning to write short stories with a contextual approach through technical news photos. The method used in this research is qualitative and quantitative research methods. The results showed two things. First, increase the ability of students to write short stories showed a high intensity and good. Second, the students respond well to the implementation of learning with contextual approach through technical news photos.